Pengaruh Cognitif Behavior Therapy dalam Memperkuat Empati pada Remaja dengan Perilaku Agresif - Ahyani, Latifah Nur; Astuti, Dwi (Universitas Ahmad Dahlan, 2014)
ABSTRACTAggression committed by juveniles with school background due to poorly developed conscience in teenagers , lack of impulse control , lack of sensitivity to moral values . One of the factors that can lead to aggressive behavior is aggressive models. Through CBT ( cognitive Behavior Therapy ) presented a model that negates the emergence of aggressive behavior and emphasize empathy so that individuals can replicate the model , individuals can capture the inspiration of the behavior which negates the aggression and may be granted when it appears strengthening empathy. The purpose of this study is to empirically examine the effect of CBT (cognitive behavior therapy) to strengthen empathy in adolescents with aggressive behavior. Results of data analysis showed that there are significant differences in the level of aggression between 99 % rate before getting treatment CBT (cognitive Behavior Therapy ) after getting treatment with CBT . After getting the CBT treatment aggressiveness level lower than before getting CBT treatment . Different coefficient of 4.093 with a p t of 0.001 ( p < 0,05 ). There is a significant difference in the level of empathy between the 99 % level before getting treatment after getting CBT with CBT treatment . After getting treatment CBT empathy levels higher than before getting the CBT treatment . Different coefficient of -3.916 with a p t of 0.002 ( p < 0,05 ) . The magnitude of the effect of CBT on aggressive behavior seen in the effective contribution of 23.7 % . The magnitude of the effect of CBT on empathy appears on the effective contribution of 30.8 % . Effective contribution is large enough to be considered significant .Keywords : Aggressive Behavior, CBT ( cognitive Behavior Therapy ), Empathy